2017
DOI: 10.18488/journal.1.2017.78.696.707
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Approach to Entrepreneurship Education and Training

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The core content of entrepreneurship education is not the teaching of entrepreneurial knowledge and thinking but the transformation of knowledge and thinking into the entrepreneurial ability for successful and independent entrepreneurship. Practices are the only way to find and solve problems in entrepreneurship education (Rusok et al, 2017). Meanwhile, experiences can be accumulated through practice, entrepreneurial awareness and ability can be cultivated, and theoretical knowledge can be transformed into personal experiences.…”
Section: Overview Of College Students' Ideological and Political Educ...mentioning
confidence: 99%
“…The core content of entrepreneurship education is not the teaching of entrepreneurial knowledge and thinking but the transformation of knowledge and thinking into the entrepreneurial ability for successful and independent entrepreneurship. Practices are the only way to find and solve problems in entrepreneurship education (Rusok et al, 2017). Meanwhile, experiences can be accumulated through practice, entrepreneurial awareness and ability can be cultivated, and theoretical knowledge can be transformed into personal experiences.…”
Section: Overview Of College Students' Ideological and Political Educ...mentioning
confidence: 99%
“…Cloud Computing enables users to use mobile digital textbooks anytime and anywhere to learn from a variety of materials depending on their learning ability and intellectual level. Joo [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] investigated students' perspectives to use new digital media and new services in an educational context. In this study, satisfaction with the expectation of digital textbooks increases the perception of enjoyment and usability, and enjoyment and perceived usefulness indirectly affect the persistence intention of using digital textbooks.…”
Section: Content Features and Effectiveness Of Digital Textbooksmentioning
confidence: 99%
“…This study demonstrated that digital textbooks provide diverse learning opportunities and improve learning outcomes through an experiment for two semesters at three elementary schools. Lee [4][5][6][7][8][9][10][11][12][13][14][15][16][17] suggested innovative approaches for u-Learning environment in public education with digital textbook. In this study, they surveyed the status of u-learning environment in Korea, examined the satisfaction of digital textbooks, and confirmed the satisfaction of digital textbooks through questionnaires on learning outcomes.…”
Section: Content Features and Effectiveness Of Digital Textbooksmentioning
confidence: 99%
See 1 more Smart Citation
“…Education, and entrepreneurship education (EE) in particular, is one of those domains [5]. EE is the process of promoting insight, knowledge, confidence, and skills to encourage individuals to act on and acknowledge commercial opportunities [6], [7]. EE seeks to facilitate the development of an entrepreneurial mindset and competence [8] through a range of teaching methods and strategies [5], including design thinking techniques that emphasize collaboration [9] and project-based learning [10].…”
Section: Introductionmentioning
confidence: 99%